Exchange of protein and nitrogen compounds in the bulls when feeding cellulose-contained feed - А. V. SHELEVACH; Y. F. RІVІS (Передгірне та гірське землеробство і тваринництво)
Metabolic processes in the body of cattle, in particular in the digestive tract of bulls, when feeding young grass, feed and various forms of fiber-containing feed during the spring-summer transition period are poorly understood. Young grass at this time contains a large amount of nitrogen-containing compounds, but very little readily available sugars and fiber. The content of the latter in the young grass of pastures and meadows, instead of the required for cattle 22-24% of dry matter, is only 15-18%. In addition, the fiber of young grass has very little of its structured form (associated with lignin and hemicellulose). This leads to the fact that cattle do not fully use the nitrogen available in the young grass.